Victims' Right to a Speedy Trial: Shortcomings, Improvements, and Alternatives to Legislative Protection - Mary Beth Ricke (Washington University Journal of Law & Policy, 2013)
A common problem in the prosecution of crimes against victims is that the trial is typically delayed through scheduling conflicts, continuances, and other unexpected delays throughout the course of the trial. Victims of the crimes are already heightened emotionally with anxiety and anticipation of the impending trial, and these delays lead to further and unnecessary trauma. Several states include victims’ bills of rights in their constitutions or enact statutes in an attempt to acknowledge and protect a victim’s interest in a speedy trial. Other states have done the same, but for only a specified class of victims, particularly child victims. While more states should enact similar legislation or include a similar bill of rights in their constitutions, the problem with these existing bills of rights and statutes is that they are under-utilized and go largely unnoticed. This Note proposes that these statutes and bills of rights should be used more frequently and be given more authority for several reasons. First, the four-factor test determining if a defendant’s right to a speedy trial has been violated is also relevant in determining if the victim’s right to a speedy trial has been violated. In other words, the interests of the defendant and victim in having a speedy trial may sometimes overlap, thus suggesting that the victim’s right to a speedy trial should be held in high regard and held with great importance as well. Second, many studies demonstrate the negative effects of prolonging the trial on the victim and on his or her ability to cope and heal from the trauma. Finally, there are practical aspects to the integrity of the judicial process that are affected when a trial is prolonged unnecessarily. This Note proposes alternative means to achieve the desired result when the victims’ bills of rights and statutes fail or fall short, principally through the use of victim advocates and counselors. Part II of this Note examines the Sixth Amendment right defendants have to a speedy trial, the evolution of the test in determining if a violation of this right has occurred, and a discussion of the current four-factor test. Part II then discusses the states where victims’ bills of rights and victims’ rights statutes have been enacted, focusing on the State of Arizona and the victims’ bill of rights enacted there. Part II also discusses the legislative intent and purpose behind the Arizona bill of rights and explains how the bill of rights was applied and analyzed in a Supreme Court case. Part III critiques the current use of victims’ bills of rights and argues why the utilization must be more widespread. It then discusses alternative ways to reach the purpose behind victims’ bills of rights— particularly the right to a speedy trial—through other means.
Keywords: criminal trial; speedy trial; trial delays; jennifer hudson; Sixth Amendment; Fourteenth Amendment